1985
DOI: 10.1159/000183469
|View full text |Cite
|
Sign up to set email alerts
|

Plasmapheresis and Dipyridamole for Recurrent Focal Glomerular Sclerosis

Abstract: A 38-year-old man had recurrence of nephrotic syndrome with focal glomerular sclerosis (FGS) in two consecutive cadaveric renal allografts. His first graft was lost to recurrent disease after 30 months. Because prior animal experiments performed when he had his first graft indicated a possible serum factor or factors capable of enhancing urine protein excretion, three plasmapheresis periods of 6–8 treatments each were performed 3,23 and 34 months after recurrence of FGS in the second graft. Urine protein excre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…There are few data on treatment of second or third recurrence of FSGS in the transplant kidney. However, several case reports indicate that response to apheresis in subsequent relapse may be as good as with ®rst relapse [4,10,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few data on treatment of second or third recurrence of FSGS in the transplant kidney. However, several case reports indicate that response to apheresis in subsequent relapse may be as good as with ®rst relapse [4,10,13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, apheresis appears to have a long-term positive eect. Protein excretion can continue to decline even after conclusion of apheresis [6,12,13]. However, it is important to adapt the apheresis regimen to the patient's clinical response.…”
Section: Discussionmentioning
confidence: 99%
“…A circulating humoral factor may be involved in the pathogenesis of FGS in some cases [18,19]. In a number of studies, plasmapheresis has been shown to have a beneficial effect in patients with recurrent FGS after renal transplantation [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…In a number of studies, plasmapheresis has been shown to have a beneficial effect in patients with recurrent FGS after renal transplantation [18][19][20]. Recently, Feld et al [1] have reported that plasmapheresis diminished proteinuria and stabilized renal function in a small group of patients with steroid-resistant idiopathic FGS.…”
Section: Discussionmentioning
confidence: 99%
“…Despite research into this causative factor remaining in a status of "cold case", PE is still a cornerstone in FSGS recurrence treatment, since the 1985 report of its first positive application by Zimmerman [30] . A systematic review by Ponticelli [4] showed that PE promotes partial or complete remission in 70% of children and 63% of adults with FSGS recurrence.…”
Section: Plasma Exchangementioning
confidence: 99%